FORMULA OPTIMIZATION AND ACTIVITY EVALUATION OF GOTU KOLA \TEXTIT{CENTELLA ASIATICA} (L.) URB AND CELERY \TEXTIT{APIUM GRAVEOLENS} L. ETHANOLIC EXTRACTS IN O/W NANOEMULSION AS HAIR GROWTH PROMOTER - Khalielah Burhani, Farwah
Celery and gotu kola are commonly used herbs proposed to stimulate hair growth. For enhancing hair follicle targeting, the ethanolics extracts of these herbs were formulated as O/W nanoemulsion. Nanoemulsion formula consisted of virgin coconut oil, Tween 80 and PEG 400 as oil phase, surfactant, and cosurfactant, respectively. The optimization process was conducted to obtain a stable nanoemulsion. Evaluation nanoemulsion consisted of the measurement of density,sentrifugation test, freeze and thaw test, accelerated stability test at 400C and room temperature, long-term stability test at 40C, skin primary irritation test and activity study (in vitro and in vivo study). In vivo and in vitro study was done by measuring the length and weight of hairs (for in vivo study only) of male Wistar rats for 21 days. Nanoemulsions of celery-gotu kola had the density of 1.044 g/mL. The result of centrifugation showed insignificant change of globule size. The result of freeze and thaw studies and accelerated stability test at 400C indicated that globules of nanoemulsion increased by the time. In the other hand, accelerated stability test at room temperature and long-term stability test at 40C indicated that globules of nanoemulsion were stable. The skin primary irritation test indicated that nanoemulsion formula was nonirritant. The test group given the nanoemulsion of celery-gotu kola showed hair growth enhancement, which were 66.47%, 31.75%, dan 28.84%, at day 7, 14, and 21, respectively. Meanwhile the test group given minoxidil as a positive control showed the highest rate of hair growth, which were 85.29%, 55.32%, and 27.10% at day 7, 14, and 21, respectively. The group given nanoemulsion of celery-gOtu kola and minoxidil showed hair growth enhancement higher than their single and mixed ethanolics extracts. The in vitro studies wasn't good enough for screening nanoemulsion activity as hair growth promoter. The combination of celery and gotu kola in the form of nanoemulsions has the ability to improve hair growth better than their single and mixed ethanolics extracts suggesting the success of hair follicle targeting.